Length of caring duration increases burden and reduces health status of cancer patients’ family caregivers in Surabaya, Indonesia - Yesiana Dwi Wahyu Werdani (Universitas Udayana, 2020)
Background and purpose: The duration of care taking of cancer patients can trigger stress which impacts on the emergence of a burden which further affects the physical health of the family caregivers. This study aims to determine the effect of caring duration on the burden and health status of cancer patient’s family caregivers. Methods: This was a cross-sectional study. Samples were 56 cancer patient’s family caregivers who were selected by a purposive sampling technique based on specified inclusion criteria from two public health centers (PHCs) in Surabaya Indonesia. Participants completed the questionnaire which comprised of questions on caring duration, caregiver burden scale and physical health status. Statistical tests using simple linear regression and multiple linear regression were performed. Results: The average age of family caregivers was 49.91 (SD=12.24), mostly female (66.7%), while half of the patients (51.8%) were a stage III cancer patients and the most frequent type of therapy (35%) received was chemotherapy. The average of caring duration was 4.44 (SD=1.92) years, score of burden was 51.07 (SD=18.45) and score health status was 60.32 (SD=10.81). After adjusted for age, gender, cancer stage and type of therapy, caring duration was significantly associated with increased burden of family caregivers (b=9.186, 95%CI: 7.85-10.10, p<0.001) and with reduced health status (b=5.282, 95%CI: 4.50-5.85, p< 0.001) Conclusion: The longer caring duration of cancer patients causes a higher burden and also a lower health status of family caregivers. Health workers and community have an important role in reducing the burden and improving the health status of caregivers by providing supports and appropriate prevention measures.